2016
DOI: 10.1037/xhp0000201
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous rhythms influence interpersonal synchrony.

Abstract: Interpersonal synchrony, the temporal coordination of actions between individuals, is fundamental to social behaviors from conversational speech to dance and music-making. Animal models indicate constraints on synchrony that arise from endogenous rhythms: Intrinsic periodic behaviors or processes that continue in the absence of change in external stimulus conditions. We report evidence for a direct causal link between endogenous rhythms and interpersonal synchrony in a music performance task, which places high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
106
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(122 citation statements)
references
References 29 publications
15
106
1
Order By: Relevance
“…In the particular case of the Path graph, we found that the group whose members had natural frequencies closer to each other (Group 1) synchronised better. This extends to multiplayer scenarios the results of [51], which showed that greater interpersonal synchrony in musical duo performances is achieved when the endogenous rhythms of two pianists are closer to each other.…”
Section: Discussionsupporting
confidence: 64%
“…In the particular case of the Path graph, we found that the group whose members had natural frequencies closer to each other (Group 1) synchronised better. This extends to multiplayer scenarios the results of [51], which showed that greater interpersonal synchrony in musical duo performances is achieved when the endogenous rhythms of two pianists are closer to each other.…”
Section: Discussionsupporting
confidence: 64%
“…We assume that, in the context of a joint (duet) performance, two musicians attempt to perform at the same frequency, but there may be natural frequency differences between them, such that one tends to play slightly faster than the other, consistent with empirical findings of frequency differences (x 1 À x 2 ) between performers that influence synchronization Zamm et al, 2016). For desynchronization to occur, we assume a slight difference between the voices, and the oscillator frequencies were set to x 1 = 2p/250, x 2 = 2p/251 rad/ms (larger values are faster).…”
Section: Frequency Of Each Oscillator Xmentioning
confidence: 78%
“…Success in joint action tasks is hypothesized to require the ability to monitor the timing of one’s own actions to predict or track the timing of another person’s action (Keller, Novembre, & Hove, 2014 ; Sebanz & Knoblich, 2009 ). Some have proposed that individual differences in interpersonal synchronization abilities are related to individuals’ spontaneous rates of movement (Loehr & Palmer, 2011 ; Zamm, Wellman, & Palmer, 2016 ), their ability to predict the timing of stimulus onsets (Mills, van der Steen, Schultz, & Keller, 2015 ; Pecenka & Keller, 2011 ), equality of social status (Demos, Carter, Wanderley, & Palmer, 2017), musical imagery (Keller & Appel, 2010 ), or their musical expertise (Franěk, Mates, Radil, Beck, & Pöppel, 1991 ; Krause, Pollok, & Schnitzler, 2010 ). Such individual differences are thought to help regulate one’s own timing as well as predicting and tracking the timing of others’ actions.…”
Section: The Role Of Musical Expertise and Sensory Feedback In Beat Kmentioning
confidence: 99%